Chitosan-based nanoparticles as delivery-carrier for promising antimicrobial glycolipid biosurfactant to improve the eradication rate of Helicobacter pylori biofilm. Issue 6 (8th January 2021) - Arif, Muhammad; Sharaf, Mohamed; Samreen,; Khan, Sohaib; Chi, Zhe; Liu, Chen-Guang
Abstract: Driven by the need to find alternatives to control H. pylori infections, this work describes the development of chitosan-PMLA nanoparticulate systems as carriers for antimicrobial glycolipid. By using a simple ionic gelation method stable nanoparticle was obtained showing an encapsulation efficiency of 73.1 ± 1.3% and an average size of 217.0 ± 15.6 nm for rhamnolipids chitosan-PMLA nanoparticles (RL-CS-NPs). Glycolipid incorporation and particle size were correspondingly corroborated by FT-IR and TEM analysis. Rhamnolipids chitosan nanoparticles (RL-CS-NPs) presented the highest antimicrobial effect towards H. pylori (ATCC 26695) exhibiting a minimal inhibitory concentration of 132 µg/mL and a biofilm inhibition ability of 99%. Additionally, RL-CS-NPs did not interfere with human fibroblasts viability and proliferation under the tested conditions. The results revealed that the RL-CS-NPs were able to inhibit bacterial growth showing adequate cytocompatibility and might become, after additional studies, a valuable approach to fight H. pylori biofilm related-infections.